The causal relationship between type 2 diabetes mellitus and isolated REM sleep behavior disorder: results from multivariable and network Mendelian randomization analysis - Zhang, Ru-Yu; Li, Jin-Yu; Liu, Yu-Ning; Zhang, Zi-Xuan; Zhao, Jie; Li, Fu-Jia (Frontiers in Endocrinology, 2024)
Objectives: To investigate the causal relationship between type 2 diabetes mellitus (T2DM, exposure) and isolated REM sleep behavior disorder (iRBD, outcome).Methods: Genome-wide association study (GWAS) data for iRBD comprised 9,447 samples, including 1,061 iRBD cases from the International RBD Study Group. Initially, we performed linkage disequilibrium score regression (LDSC) to explore the genetic correlation between T2DM and iRBD. Then the two-sample univariate MR (UVMR) analysis was conducted to examine the effects of T2DM and blood sugar metabolism-related factors on iRBD. Subsequently, we applied multivariable MR (MVMR) methods to further adjust for confounders. Lastly, we executed a network MR analysis, with cytokines and immune cell characteristics as potential mediators, aiming to investigate indirect effect of T2DM on iRBD.Results: Results from LDSC suggest a genetic correlation between T2DM and iRBD (rg=0.306, P=0.029). UVMR analysis indicates that both T2DM (Odds Ratio [95% Confidence Interval] = 1.19 [1.03, 1.37], P = 0.017) and high blood glucose levels (1.55 [1.04, 2.30], P = 0.032) are risk factors for iRBD. Even after adjusting for confounders in MVMR, the association between T2DM and iRBD remains robust. Finally, results from network MR analysis suggest that T2DM may indirectly promote the development of iRBD by reducing levels of Stromal Cell-Derived Factor 2 in circulation and by increasing BAFF-receptor expression in IgD-CD38-B cells.Conclusions: T2DM may promote the onset of iRBD by influencing immune-inflammatory responses. Our findings provide valuable insights and directions for understanding the pathogenesis of iRBD, identifying high-risk groups, and discovering new therapeutic targets.